Pelatihan Pembuatan Dashboard Dan Tiktok Bisnis Pada UMKM Shofi Cookies - Sari, Syandra; Sugiarto, Dedy; Shofiati, Ratna; Ariwibowo, Anung Barlianto; Gunawan, Muhammad Ichsan; Shan ASP, Putri; Jubaedah, Ida; Firdasari, Elita Wahyu; Nadia, Alya Shafa (Pusat Riset dan Inovasi Nasional, 2023)
The Community Service Program (PKM) has successfully conducted a training on Dashboard Development and TikTok Business for the Small and Medium Enterprise (MSMEs) Shofi Group. This training was facilitated by the Informatics Engineering Department of Trisakti University and has received an excellent rating based on feedback from the participants. As part of this training, a visualization dashboard was successfully integrated into the Shofi Group's website, allowing them to monitor sales data more efficiently and effectively. In addition, participants also learned about the use of TikTok Business as a tool for marketing their products. Positive feedback from Shofi Group indicates the significant benefits of this training, in terms of assisting MSMEs to adapt and utilize digital technology in their business development. These results underline the importance of similar programs in supporting SMEs to compete in the digital era. It is hoped that the success of this PKM can lay the foundation for similar initiatives in the future, supporting more MSMEs in leveraging the potential of digital technology.